Will We be Helped from Abroad? A Case of Visceral Leishmaniasisis in Crimea - I.V. Bogadelnikov; S.V. Usova; A.V. Bobrysheva; Т.N. Bezdolnaya; Ye.M. Soboleva (Zaslavsky O.Yu., 2013)
The article presents a case of non-endemic, rare disease in the Crimea - the visceral form of leishmaniasis in 11-month-old child, which clinically occurs with prolonged fever, hepatolienal syndrome with manifestations of hepatitis, anemia, thrombocytopenia. Establishing final definitive diagnosis was preceded by diagnoses: acute intestinal infection, salmonellosis, hepatitis, fever of unknown origin, cytomegalovirus infection. The final diagnosis - visceral leishmaniasis was made in Israel by the results of liver biopsy with the discovery of Leishman - Donovan bodies. The child was treated with AmBisome (liposomal amphotericin B). After the treatment the child with his recovery returned to Ukraine. It is suggested that the above incident was a manifestation of the course of multicomponent non-cyclic infectious process.